2005
DOI: 10.1073/pnas.0409626102
|View full text |Cite
|
Sign up to set email alerts
|

A vital role of tubulin-tyrosine-ligase for neuronal organization

Abstract: Tubulin is subject to a special cycle of detyrosination͞tyrosination in which the C-terminal tyrosine of ␣-tubulin is cyclically removed by a carboxypeptidase and readded by a tubulin-tyrosine-ligase (TTL). This tyrosination cycle is conserved in evolution, yet its physiological importance is unknown. Here, we find that TTL suppression in mice causes perinatal death. A minor pool of tyrosinated (Tyr-)tubulin persists in TTL null tissues, being present mainly in dividing TTL null cells where it originates from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
305
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 261 publications
(322 citation statements)
references
References 41 publications
14
305
0
3
Order By: Relevance
“…Tubulin is also modified by post-translational phosphorylation and detyrosynation, as well as addition of tyrosine (Raybin and Flavin, 1977a;b), mono-and poly-glutamine (Audebert et al, 1993;Edde et al, 1990), and glycine (Plessmann and Weber, 1997) (see also (Luduena, 1998) for an overview of tubulin modifications). Some of these tubulin modifications have been associated with microtubule stability and found to serve as markers for cell polarization (Erck et al, 2005;Gundersen and Bulinski, 1986;Infante et al, 2000;Khawaja et al, 1988). Tubulin modifications by amino acids have also been implicated in modulation of microtubule functions in various types of motile cells (Ikegami et al, 2007;Raybin and Flavin, 1977a;b;Redeker et al, 2005).…”
Section: Posttranslational Regulation Of Cell Migrationmentioning
confidence: 99%
“…Tubulin is also modified by post-translational phosphorylation and detyrosynation, as well as addition of tyrosine (Raybin and Flavin, 1977a;b), mono-and poly-glutamine (Audebert et al, 1993;Edde et al, 1990), and glycine (Plessmann and Weber, 1997) (see also (Luduena, 1998) for an overview of tubulin modifications). Some of these tubulin modifications have been associated with microtubule stability and found to serve as markers for cell polarization (Erck et al, 2005;Gundersen and Bulinski, 1986;Infante et al, 2000;Khawaja et al, 1988). Tubulin modifications by amino acids have also been implicated in modulation of microtubule functions in various types of motile cells (Ikegami et al, 2007;Raybin and Flavin, 1977a;b;Redeker et al, 2005).…”
Section: Posttranslational Regulation Of Cell Migrationmentioning
confidence: 99%
“…The following primary antibodies were used in this study: mAb against ␣-tubulin (alpha3a clone (12), ascitic fluid, dilution 1/1,000 for immunofluorescence); mAb 175 against C-terminal part of N-STOP (6) (dilution 20 g/ml for immunofluorescence and 1 g/ml for Western blot); affinity-purified phospho-STOP P2 and P4 antibodies (dilution 20 g/ml for immunofluorescence and 1 g/ml for Western blot); P1 mAb against phospho-STOP (hybridoma culture supernatant, dilution 1/10 for Western blot); mAb against CaMKII (Ref C89220, Transduction laboratories), Homer (all isoforms, Chemicon), synapsin1 (BD Biosciences), CaMKI and CaMKIV (Santa Cruz Biotechnology) were used following manufacturer's advice.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, in neurons and fibroblasts isolated from TTL-null mice, increased levels of detyrosination resulted in mislocalization of CLIP-170 and p150Glued whereas other +TIP proteins such as EB1 were unaffected. 81,82 CLIP-170 and p150Glued both have a CAP-Gly domain. Structural work has shown that the CAP-Gly domain has a binding groove that may directly recognize the unmodified C-terminal sequence of a-tubulin.…”
Section: Who Are the Interpreters Of The Tubulin Code?mentioning
confidence: 99%